2017
DOI: 10.1021/acs.organomet.6b00935
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Exchange in Intramolecular Lewis Pairs with Multiple Lewis-Acidic Functions

Abstract: Hydroboration of allyldimethylamine, diallylmethylamine, triallylamine, and diallylmethylphosphane with dimeric 9-BBN yielded the corresponding singly, doubly, and triply Lewis-acid-functionalized intramolecular Lewis pairs. For the singly Lewis-acid-functionalized derivative Me2N­(CH2)3-9-BBN no evidence for the existence of an equilibrium involving an open-chain form was found in solution. For the doubly and triply Lewis-acid-functionalized compounds Me3–x E­[(CH2)3-9-BBN] x [E = N (x = 2, 3), P (x = 2)] a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…13 support the purity, the obtained lower value of C can be because of incomplete combustion. 37,38 However, the purity was confirmed by 1 H and 13 C spectra. Synthesis of 2-(9-Borabicyclo[3.3.1]non-9-ylmethyl)-1methyl-1H-imidazole Dimer, 2.…”
Section: ■ Experimental Sectionsupporting
confidence: 65%
See 2 more Smart Citations
“…13 support the purity, the obtained lower value of C can be because of incomplete combustion. 37,38 However, the purity was confirmed by 1 H and 13 C spectra. Synthesis of 2-(9-Borabicyclo[3.3.1]non-9-ylmethyl)-1methyl-1H-imidazole Dimer, 2.…”
Section: ■ Experimental Sectionsupporting
confidence: 65%
“…Found: C, 70.88; H, 10.01; N, 12.93. Similar to compound 1 , the elemental analysis values of H and N support the purity, and the obtained lower value of C can be because of incomplete combustion. , In this case also, the purity was confirmed by 1 H and 13 C spectra.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In sharp contrast, a significant difference was clearly observed for the bifunctional catalyst 3b , wherein a broad resonance (fwhm = 1371 Hz) with a slight upfield chemical shift (Δδ = −0.34 ppm) was observed. This phenomenon indicates the existence of an interaction between the intramolecular quaternary ammonium salt and the boron center …”
Section: Resultsmentioning
confidence: 90%
“…While triphenyl phosphine does not react with water under ambient conditions, we found that a bisborane-functionalized triaryl phosphine can instantaneously and quantitatively reduce water to generate dihydrogen and phosphine oxide. [46][47][48][49] This reaction features an electron relay mechanism among the borane-phosphine-borane centers, which allowed an umpolung of a proton in water to a hydride on borane driven at a phosphonium center. This then led to formation of phosphine oxide and H 2 , leaving both Lewis acidic boranes intact after the reaction.…”
Section: Introductionmentioning
confidence: 99%